2021
DOI: 10.1002/job.2538
|View full text |Cite
|
Sign up to set email alerts
|

Why people engage in supplemental work: The role of technology, response expectations, and communication persistence

Abstract: Summary Supported by various collaboration technologies that allow communication from any place or time, employees increasingly engage in technology‐assisted supplemental work (TASW). Challenges associated with managing work and nonwork time have been further complicated by a global pandemic that has altered traditional work patterns and locations. To date, studies applying a TASW framework have focused mainly on individual uses of technology or connectivity behaviors and not considered the potential team and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…The use of Google Drive was measured using four items (van Zoonen, Sivunen, & Treem, 2021; van Zoonen, Sivunen, Rice, & Treem, 2021). A sample item is, “I use Google Drive to collaborate on shared files.” Respondents were asked to indicate the frequency with which they used Google Drive for the specified activities in the past 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The use of Google Drive was measured using four items (van Zoonen, Sivunen, & Treem, 2021; van Zoonen, Sivunen, Rice, & Treem, 2021). A sample item is, “I use Google Drive to collaborate on shared files.” Respondents were asked to indicate the frequency with which they used Google Drive for the specified activities in the past 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…However, this also raises the question of whether after‐hour connectivity is the result of a workplace demand that employees address at their discretion, or whether after‐hour connectivity is tethering employees to their work, including after hours. Understanding the relationship between connectivity, autonomy and well‐being is increasingly important at times when boundaries between work and nonwork are particularly porous (van Zoonen et al, 2021). We specifically focus on connectivity behaviour that extends beyond the workday (e.g., Boswell & Olson‐Buchanan, 2007; Büchler et al, 2020; Mazmanian et al, 2013), rather than connectivity during work (e.g., Sonnentag et al, 2018; Ten Brummelhuis et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…Empirical studies have shown that bringing work home to perform supplemental overtime work can increase time pressure and psychological distress (Duxbury et al, 1996;Ojala et al, 2014). Organizational research has found connections between supplemental work from home and team-level response expectations, suggesting that people do supplemental work at home because of work pressure and, at the same time, this intensifies work pressure (Zoonen et al, 2021).…”
Section: Indirect Associations Of Working From Home With Parenting Pr...mentioning
confidence: 99%